HUBUNGAN KEKUATAN OTOT LENGAN TERHADAP KETEPATAN SERVIS PANJANG DALAM PERMAINAN BULU TANGKIS - Mahatma Raison Pribadi; Alief Lam Akhmady (Jurnal Pendidikan dan Ekonomi (JUPEK), 2026)
The Relationship between Arm Muscle Strength and Long Service Accuracy in Badminton Games for Sports Education Students (ISDIK) Kie Raha, North Maluku. This study uses an observation method with correlation analysis techniques. The results of the test data calculation of the two variables of arm muscle strength and long service accuracy in badminton games can be obtained r-count of 1.009. These results are then compared with r table at a significance level of α = 0.05% with dk - n - 1 = 29, namely 0.367 and 0.470 at a significance level of α - 0.01%. Thus r count = 1.009 > r table - 0.367 and 0.470, so it can be concluded that the research hypothesis or alternative hypothesis (Ha) is accepted and the null hypothesis (H0) is rejected. In other words, the research hypothesis proposed in this study is: There is a significant relationship between arm muscle strength and long service accuracy in badminton games for Sports Education Students (ISDIK) Kie Raha, North Maluku